Non-Invasive Methods of Haemodynamic Monitoring - Urbańczuk, Marcin; Urbańczuk, Magdalena; Tuzim, Tomasz; Schab, Katarzyna; Tuzim, Kamila; Lewicki, Marcin (Journal of Education, Health and Sport, 2018)
Diseases of the cardiovascular system are one of the most common causes of death in Poland and in the world. Along with the progress of medicine and development of diagnostic methods, there are a growing number of useful procedures allowing for better monitoring of patient’s cardiovascular parameters and thereby more effective treatment. Monitoring of haemodynamic parameters of the circulatory system is necessary in patients hospitalised in anaesthesiology departments and in most intensive cardiac care units. The methods employed to evaluate the work of the heart can be divided into invasive and non-invasive, depending on whether they require a disruption of the continuity of the patient’s tissues. In view of the ease of implementation of non-invasive methods, their costs and their implementability in practically every patient, these methods are used with increased frequency, both in patient care, as well as in measurements taken for scientific purposes. In recent years, several new methods have been developed which in many aspects are by no means inferior to the "golden standard" constituted by the invasive methods. When supported by medical knowledge and experience of health care professionals, they become particularly useful and valuable for improving medical care. This paper presents the latest of the currently available methods of haemodynamic monitoring. The mechanism of action of each of them has been explained, as well as the possibilities they present, the limitations they hold and the examples of their use in patient care.